Health-Related Quality of Life Measurement Tools, Predictors and Modifiers - Mullings, Jasneth; Arbor, Sage; Cumbay, Medhane (IntechOpen, 2022)
The concept of health-related quality of life (HRQoL) has evolved since the 1980s, with broad-based applications for clinical care, research, and health policy, as well as for individual and patient use. This book, Health-Related Quality of Life - Measurement Tools, Predictors and Modifiers, highlights measurement tools for HRQoL, as well as predictors and modifiers, examining HRQoL in various disease states, including psychological health. It also discusses ethical issues in the use of HRQoL measurements. The book is a compendium of original research, sharing perspectives from across developing and developed world settings. It is a useful text for researchers and students of academic disciplines in public health and clinical studies, extending to healthcare administrators and policymakers.